(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
A relationship between psychological characteristics and optimal performance states, indicating that elite and successful sports participants are more motivated, committed, self-confident, focused and able to peak under pressure compared to non-elite and less successful participants. The mental aspects of performance of functional activities in sport may be improved by the constructive implementation of mental-skill instruction. Personalized mental skills preparation helps learners to consider their cognitions in order to enable a degree of flow across the various mood states of involvement in the organization and implementation of task-related skills. A participant’s capacity to regulate the competition-related behavioral emotional dimensions not only enhances mission success but also acts as a mental keystone to self-belief well-being.